Concordance between the assessment of Aβ42, T‐tau, and P‐T181‐tau in peripheral blood neuronal‐derived exosomes and cerebrospinal fluid. Issue 8 (1st August 2019) - Jia, Longfei; Qiu, Qiongqiong; Zhang, Heng; Chu, Lan; Du, Yifeng; Zhang, Jiewen; Zhou, Chunkui; Liang, Furu; Shi, Shengliang; Wang, Shan; Qin, Wei; Wang, Qi; et al.
Abstract: Introduction: Neuronal‐derived exosomal Aβ42, T‐tau, and P‐T181‐tau have been demonstrated to be biomarkers of Alzheimer's disease (AD). However, no study has assessed the association of Aβ42, T‐tau, and P‐T181‐tau between exosomes and CSF. Methods: This was a multicenter study with two‐stage design. The subjects included 28 AD patients, 25 aMCI patients, and 29 controls in the discovery stage; the results of which were confirmed in the validation stage (73 AD, 71 aMCI, and 72 controls). Results: The exosomal concentrations of Aβ42, T‐tau, and P‐T181‐tau in AD group were higher than those in aMCI and control groups (all P  < .001). The level of each exosomal biomarker was highly correlated with that in CSF. Discussion: This study verified the agreement between CSF and blood exosomal biomarkers and confirmed that exosomal Aβ42, T‐tau, and P‐T181‐tau have the same capacity as those in CSF for the diagnosis of AD and aMCI.